Asymmetric Aldol Reaction of Thiazole‐Carbaldehydes: Regio‐ and Stereoselective Synthesis of Tubuvalin Analogues. Issue 16 (26th September 2014) - Paladhi, Sushovan; Das, Joydeb; Samanta, Mousumi; Dash, Jyotirmayee
Abstract The first organocatalytic enantioselective approach to precursors of tubuvaline (pre‐Tuv) is presented employing a prolinamide‐catalyzed aldol reaction of easily accessible thiazole‐carbaldehyde with methyl isopropyl ketone "on water" in excellent yield as well as regio‐ and enantioselectivities. The analogues of pre‐Tuv were achieved using an L‐proline‐catalyzed direct asymmetric aldol reaction of substituted thiazole‐carbaldehydes with acetone. A direct and flexible approach to the tubavaline (Tuv) core of tubusylins has been established employing the reductive amination of the pre‐Tuv species. The key aldol reaction should greatly expand the potential of this strategy to the synthesis of natural product tubulysins and a range of analogues. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>